Monitoring accumulative fatigue and recovery status in elite field hockey players during different phases of a competitive season - De Villiers, Louise Adriana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScSportSc)--Stellenbosch University, 2014.